Establishment of optimum biofertilizer's parametric conditions for the plantations of fruit, essential oil and herb plants - Che Man, Rohaida; Yunus, Rosli Mohd; Sulaiman, Siti Zubaidah; Shaarani, S. M.; Zakil, Fathie Ahmad; Abdul Mudalip, S. K. (2011)
In recent years, there has been increasing concern regarding the chemical impact of agricultural activities on the environment. So it is necessary to identify the optimum dosage of fertilizer application to avoid the exceeding dosage which can cause the contaminants and environmental pollution. The objective of this study is to optimized the biofertilizer usage in terms of dosage and application frequency to gain the optimum production of Roselle, Patchouli and Asiatica pennywort plants. These three plants represent three different group of plants which were; Roselle from fruit plants, Patchouli from essential oil plants while Asiatica pennywort from the herbs plant, respectively. In this research, the Design of Experiment (DOE) software was used in optimization and analysis process. Based on the result and data analysis, it is found that dosage at five gram and application frequency at seven days resulted the highest oil yield of roselle seeds which is 0.026% while dosage at 25 gram and application frequency at 28 days resulted the highest oil yield for Patchouli. plants which is 4.34%, respectively. Unfortunately, no valid result was found for Asiatica pennywort plants because of natural error mostly the highest temperature of weather along the research period.